Nitrodrenové hrebování tibiálními hreby Medin - Palarcík, J; Veselý, R; Trupar, E (Rozhledy v chirurgii, 2000)
In a prospectively followed up group of 163 nailed tibiae in 157 casualties after 4-48 months, on average after 15 months following implantation 20 patients (12.5%) developed complications. In two instances the nail broke or was bent (1.25%), the remaining complications were not associated with the implant or instruments. Subsequent tests however did not prove defective material of the damaged nails. Medin nails are a reliable, readily available and cheap implant.
Keywords: Humans; fraktury tibie; lidé středního věku; Tibial Fractures; Female; Aged; intramedulární fixace fraktury; dospělí; senioři; lidé; Bone Nails; Adult; kostní hřeby; ženské pohlaví; Male; Middle Aged; Adolescent; Aged, 80 and over; senioři nad 80 let; mužské pohlaví; Fracture Fixation, Intramedullary; mladiství